2017
DOI: 10.1155/2017/1378175
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Power of Nrf2 and PPARγ Activators against Metabolic and Drug‐Induced Oxidative Injury

Abstract: Mammalian cells have evolved a unique strategy to protect themselves against oxidative damage induced by reactive oxygen species (ROS). Especially, two transcription factors, nuclear factor erythroid 2p45-related factor 2 (Nrf2) and peroxisome proliferator-activated receptor γ (PPARγ), have been shown to play key roles in establishing this cellular antioxidative defense system. Recently, several researchers reported ameliorating effects of pharmacological activators for these Nrf2 and PPARγ pathways on the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
103
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 111 publications
0
103
0
Order By: Relevance
“…PPARγ may bind to specific elements in the promoter region of genes it regulates, including Nrf2, catalase (CAT), glutathione S-transferase (GST), heme-oxygenase-1 (HO-1), and manganese-dependent superoxide dismutase (Mn-SOD). In contrast, Nrf2 can regulate PPARγ expression by binding to the PPARγ promoter in the sequence of antioxidant response elements (ARE) that are located in the -784/-764 and -916 regions of the PPARγ promoter [89,90]. The reduction in PPARγ expression in Nrf2 knockout mice provides confirmation of this regulation [91].…”
Section: Pparγ Receptormentioning
confidence: 99%
“…PPARγ may bind to specific elements in the promoter region of genes it regulates, including Nrf2, catalase (CAT), glutathione S-transferase (GST), heme-oxygenase-1 (HO-1), and manganese-dependent superoxide dismutase (Mn-SOD). In contrast, Nrf2 can regulate PPARγ expression by binding to the PPARγ promoter in the sequence of antioxidant response elements (ARE) that are located in the -784/-764 and -916 regions of the PPARγ promoter [89,90]. The reduction in PPARγ expression in Nrf2 knockout mice provides confirmation of this regulation [91].…”
Section: Pparγ Receptormentioning
confidence: 99%
“…The Nrf2 pathway plays an important role in the defense against oxidative stress injury (24). Therefore, the protein expressions of Nrf2 (nuclear), Nrf2 (total) and its downstream molecule HO-1 in human melanocytes were analyzed to determine its role in PM2.5-induced oxidative stress injury.…”
Section: Pm25 Induces the Oxidative Stress Response In Human Melanocmentioning
confidence: 99%
“…Additionally, increased evidence suggested that Nrf2 signaling pathway is an important modulator in anti-inflammatory responses. The activation of Nrf2 signaling was showed to prevent inflammation and inflammatory cell infiltration and reduce organ injuries [27]. Therefore, we investigate whether MitoQ can protect against LPS-induced oxidative insults through activating Nrf2 signaling pathway.…”
mentioning
confidence: 98%